Rural water supply in Ethiopia: A political economy analysis - Florence Pichon (Overseas Development Institute (ODI), 2019)
Many rural communities in sub-Saharan Africa still lack clean water for basic needs such as drinking and washing. Even where water points have been constructed, many break down prematurely or provide inadequate, seasonal or poor quality water supplies. While techno-managerial factors are relevant in explaining these problems, attention needs to be paid to the institutional and political-economic dynamics shaping policy outcomes on the ground. This study examines the political economy of rural water supply in Ethiopia, using a literature review and interviews with government staff and water sector stakeholders to unpick systemic obstacles to sustainable access to water. It reccomends that sector stakeholders: inform and build on the 2018 National WASH Inventory, invest in water resource mapping and monitoring, support legalisation of Water and Sanitation Committees and aim to improve accountability, leverage drought events to reframe the conversation.
Keywords: 330